Whither the public Internet? - William Lehr; David Clark; Steve Bauer; Arthur Berger; Philipp Richter (International Telecommunications Society (ITS), 2018)
This paper addresses the question of what should be meant by the phrase the Internet, or equivalently, the public Internet. Since its origins in the 1960s, the Internet has changed significantly in terms of the networks and technologies, services that are supported, and industry players who participate in the Internet ecosystem, growing in global economic and social importance. This paper discusses the changing role of the network operators and service providers that support the public Internet, and the relationship between what might be considered the public Internet and other elements of the global infrastructure. Herein, we explain why the quest for a single definition for the Internet is likely a fool's errand, while recognizing that there remains a need to understand what the concept means in light of its growing importance as a topic of policy concern. Instead of a definition, we propose a three-lens framework through which to evaluate technical and market trends that are changing the Internet and assist in determining whether those changes are or are not consistent with what we view as worth preserving in that which we refer to as the Internet.
Keywords: 330